Problems of depreciation and accounting depreciation of fixed assets in budgetary institutions of the Pridnestrovian Moldavian Republic - V. N. Chernish (Путеводитель предпринимателя)
The article discusses the relationship between the concepts ofdepreciation and amortization of fixed assets. A comparative analysis of the procedure for the depreciation in budgetary institutions and accounting ofdepreciation in commercial organizations. A method is proposed and substantiated the practical relevance of depreciation of fixed assets in budgetary institutions of the Pridnestrovian Moldavian Republic.